Study on Flexural Properties of Basalt Fiber Textile Reinforced Concrete (BTRC) Sheets Including Short AR-Glass Fibers - Zhang, Qin; Li, Sanya; Gong, Susu; Zhang, Guanhua; Xi, Guangheng; Wu, Yaoqing (Frontiers in Materials, 2020)
Experimental investigations were carried out to determine the mechanical properties of fine concrete with short AR-glass fibers including the effects of fiber content and length. Also, the basalt fiber textile reinforced concrete (BTRC) sheets with short AR-glass fibers were tested under four-point bending, and the effects of the number of fiber textile layer and fiber length on the flexure properties were emphatically analyzed. The results show that the mechanical properties of fine concrete with fibers were mainly related to fiber length and content, the mechanical properties of fibers reinforced fine concrete increase with the increase of fiber length, and the comprehensive mechanical properties of fine concrete materials are the best when the AR-glass fiber content is about 5%. The flexure performance tests of BTRC sheets show that the strength and the deformation capacity of sheets increase with the increase of the number of fiber textile layers. The short AR-glass fibers can also effectively improve the strength and deformation capacity of BTRC sheets, and the cracking load and ultimate displacement can be respectively increased by up to 106% and 268% compared with BTRC sheets without short fibers. For the multi-fiber compound reinforced concrete sheets, the fiber textile can provide tension in the desired direction, and the short AR-glass fibers can improve the cracking resistance and toughness of sheets.